Numerical Analysis of Shear Contribution of CFRP-Strengthened RC Beams by Different Bond-Slip Models - Shengqiang Ma; Jianfeng Sun; Tiancai Xu (International Journal of Concrete Structures and Materials)
Abstract During a numerical investigation conducted using ABAQUS software, various bond-slip models for the FRP–concrete interface were evaluated to accurately predict the shear contribution of FRP in strengthening reinforced concrete (RC) beams. Three established bond-slip models were chosen to develop finite element analysis models for the four FRP-strengthened beams. The outcomes of these numerical simulations were subsequently compared with experimental data. The results demonstrated a strong correlation between the finite element simulations and the experimental tests, particularly regarding the failure process and shear capacity of the reinforced beams. The increase in shear capacity observed during testing varied from 13.5% to 42.9%. In contrast, the corresponding increase in shear capacity predicted by the finite element simulations ranged from 5.5% to 47.7%. The discrepancy in CFRP shear contribution among beams with different bond-slip relationships, under identical reinforcement configurations, was observed to be within the range of 0.1% to 15.9%. The numerical results of the Nakaba model showed a higher level of safety; however, the simulation performance of the Lu model was regarded as more effective and better suited for numerical analysis in predicting the shear contribution of FRP in strengthened RC beams.